Customary Institutions as Social Agents in Strengthening Fathers’ Roles within Families in Nifaloolauru Village - Ewi Darman Ndraha; Sugito; Serafin Wisni Septiarti; Popon Aryani Sapitri; Muhammad Ihya Ulumuddin (International Journal of Educational Practice and Policy, 2026)
This study aims to identify the forms of the weakening of fathers’ roles within families experienced by children and analyze the role of traditional institutions in overcoming it. Using a qualitative approach with purposive sampling techniques, the study involved five key informants consisting of traditional leaders, children experiencing the weakening of fathers’ roles within families, and guardians. Data were collected through in-depth interviews and documentation, then analyzed through the stages of reduction, presentation, and verification.  The results show that the weakening of fathers’ roles within families in this village appears in three forms: physical absence due to the death of the father, functional absence even though the father lives at home, and emotional absence due to authoritarian parenting. Customary institutions play an important role through cultural activities such as Famaena, hendri-hendri, and Fasile, which create spaces for interaction between fathers and children, strengthen communication, and restore emotional closeness. These traditional activities serve as a means of reconstructing the role of fathers in the family, as well as a local mechanism to reduce the impact of the weakening of fathers’ roles within families.